2016
DOI: 10.3389/fpls.2016.01891
|View full text |Cite
|
Sign up to set email alerts
|

OsMADS1 Represses microRNA172 in Elongation of Palea/Lemma Development in Rice

Abstract: Specification of floral organ identity is critical for the establishment of floral morphology and inflorescence architecture. Although multiple genes are involved in the regulation of floral organogenesis, our understanding of the underlying regulating network is still fragmentary. MADs-box genes are principle members in the ABCDE model that characterized floral organs. OsMADS1 specifies the determinacy of spikelet meristem and lemma/palea identity in rice. However, the pathway through which OsMADS1 regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…This miRNA was further studied and would be discussed in a separate report. Osa‐miR172 is involved in flowering, palea/lemma development and spikelet determinacy (Zhu et al ., ; Lee et al ., ; Dai et al ., ). Osa‐miR172 was not further pursued due to its association with developmental processes.…”
Section: Resultsmentioning
confidence: 97%
“…This miRNA was further studied and would be discussed in a separate report. Osa‐miR172 is involved in flowering, palea/lemma development and spikelet determinacy (Zhu et al ., ; Lee et al ., ; Dai et al ., ). Osa‐miR172 was not further pursued due to its association with developmental processes.…”
Section: Resultsmentioning
confidence: 97%
“…The results showed that OsG1 probably functions between OsMADS50 and many other MADS-box genes, such as OsMADS32 , OsMADS18 , OsMADS34 , OsMADS65 , OsMADS5 , OsMADS14 , OsMADS15 , OsMADS1 , OsMADS6 , and OsMADS17 , to specify floral organ identity. Among these MADS-box genes, OsMADS32 regulates floral organ identity in rice, OsMADS1 plays an important role in rice floral organ identity specification and floral meristem determinacy [45, 46, 59, 60], OsMADS1 and OsMADS15 are both required to ensure sexual reproduction in rice [61], and OsMADS34 specifies the identities of floral organs [62, 63]. Based on these results, we propose that OsG1 functions synergistically with or upstream of OsMADS1 , OsMADS15 , OsMADS32 , and OsMADS34 genes to specify the identities of floral organs in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical analysis and in situ hybridization were carried out as previously described by Wang et al (2010) and Dai et al (2016) , respectively.…”
Section: Methodsmentioning
confidence: 99%